Testing the effects of aspect and total insolation on luminescence depth profiles for rock surface exposure dating. (April 2022) - Fuhrmann, S.; Meyer, M.C.; Gliganic, L.A.; Obleitner, F.
Abstract: Using luminescence to date the burial and exposure ages of rock surfaces has been a revolutionary new geochronological approach developed and refined over the past decade. Rock surface exposure dating is based on the principle that the depth to which the luminescence signal is bleached into a rock surface is dependent on the duration of that rock surface's exposure to sunlight. However, given the recentness of method development, the effects of basic light exposure variables such as the orientation of rock surfaces and the incidence angle of incoming light on bleaching depth have not been tested. We designed an experiment in which we controlled the exposure duration (t) and orientation of granite and sandstone samples while measuring the light attenuation coefficient (μ) and the photon flux at the rock surface ( φ 0 ) to determine the influence of spatial orientation of a rock surface on its respective bleaching depth. Our results confirm that the opacity of the rock (μ) and the total insolation have significant effects on the bleaching depth for vertically oriented surfaces. We also observed that the bleaching depth is strongly related to the incidence angle at which the sunlight hits the rock surface, indicating that the effectiveness of bleaching of a given rock surface follows seasonal cycles. Our data suggest that optimal calibration samples for rock surface exposure dating should be of the same lithology and have the same geographical location and orientation of the target sample. Additionally, calibration samples should be collected in year increments so that no season's solar incidence angles are preferred. Highlights: The bleaching rate in rock surfaces is strongly related to the incidence angle at which sunlight hits the rock surface. There are seasonal cycles in the effectiveness of bleaching of the luminescence signal in rock surfaces. We confirm that the bleaching depth depends on the light attenuation coefficient (µ) and the amount of total insolation.